MANAJEMEN BENCANA DI KABUPATEN INDRAGIRI HILIR (STUDI KASUS PENCEGAHAN ABRASI DI KECAMATAN TANAH MERAH) - Yanti, Trida; Yuliani, Febri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Disaster management is an action taken before, during and after a distric disaster. Indragiri Hilir is one of district in Riau Province that often experienced abrasion in several areas. Apart from being caused by the ebb and flow of river water, and caused by river currents that are so swift that eroding the surface of the land so swift that eroding the surface of the land so that the land is no longer able to withstand the loud on it. Abrasion can be affected by several factors, among them are large or small sea waves, and fast and slow sea waves. The aimed of this research was to determine how the abrasion disaster management carried out by the Indragiri Hilir Regency government and to determine the inhibiting factors in the abrasion disaster management. This research is a qualitative research with a case study approach. The collection of data required, such as primary and secondary data was collected throught interview, observation and documentation and then analyzed so that conclusions can be known from existing research problems. The reseult of this research find out that the implementation of disaster management carried out by the Indragiri Hilir Regency government represented by the Regional Disaster Management Agency (BPBD) has not been implemented optimally, this is caused by several factors, namely budget and human resources. Keywords: Disaster Management, Disaster Management Agency